Incorporating Environmental Issues in Teaching and Learning English in Ampenan (Jangkok River) - Dewi, Puspita; Yuliatin, Riyana Rizki; Ibrahim, Isra Dewi Kuntary; Satya HD, Dharma; Hadi, Sirojul; Wardhana, Helna (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
English becomes one of the most fundamental subjects should be taught in a tourist destination including in the seashore area in Ampenan (Kota Tua). Collaboration with the youth community namely Ibra and Yayasan Saling Jaga Indonesia (previously the name is Yayasan Saling Jaga Indonesia). Community has a positive impact on the area involving economic and environmental aspects. Teaching English with implementing Rubbish Payment (one of RELASI’s program) encourage children and young people to be more aware to their environment and maintain the seashore place to become a good tourism place in Mataram. Some certain materials concern on environmental matter therefore by imbedding environmental issue in the materials pursue and open up the learners’ mind to be more aware to their surroundings, particularly to the plenty of rubbish in the seashore. Communicative teaching methods and designed authentic materials used in the teaching and learning process. It is expected that this program could promote and assist the government of West Nusa Tenggara to reduce, reuse, and recycle plastics that becomes one of the most current problems in the worlds, especially in West Nusa Tenggara.